The Use of Artificial Intelligence in Financial Statement Audit - Nurul Fachriyah; Octadila Laily Anggraeni (Publikasi Indonesia, 2024)
The rapid advancement of Artificial Intelligence (AI) has transformed various industries, including financial auditing, by improving efficiency, accuracy, and fraud detection. This study investigates the extent of AI adoption in financial audits in Indonesia, with a focus on both Big 4 audit firms and smaller, local firms. Through a literature review and interviews with auditors from eight firms, the research explores the current state of AI utilization and the barriers to its implementation. The results indicate that while Big 4 firms are in the developmental phase of integrating AI into their auditing processes, smaller firms face significant obstacles, such as financial limitations, lack of expertise, and regulatory uncertainties, which hinder AI adoption. Despite the challenges, auditors from larger firms anticipate that AI will play a crucial role in future audits. The study concludes that AI adoption in Indonesian financial audits is uneven, and further efforts are required to support smaller firms through accessible AI tools, clearer regulations, and targeted training. These measures are essential for closing the gap in audit quality between large and small firms, ensuring broader AI implementation in the auditing sector.